2002
DOI: 10.1016/s1097-2765(02)00439-2
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism of Cell Survival

Abstract: Death receptors such as Fas are present in a variety of organs including liver and play an important role in homeostasis. What prevents these harmful receptors from forming homooligomers, clustering, and initiating the apoptotic pathway is not known. Here, we report the discovery of a cell survival mechanism by which Met, a growth factor receptor tyrosine kinase, directly binds to and sequesters the death receptor Fas in hepatocytes. This interaction prevents Fas self-aggregation and Fas ligand binding, thus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(55 citation statements)
references
References 26 publications
(3 reference statements)
3
52
0
Order By: Relevance
“…9A). Previous work suggested that Met-mediated prevention of apoptosis could be independent from its catalytic activity (15). Our data clearly indicate that the mechanisms by which Met triggers the antiapoptotic response are also strictly reliant on its kinase activity.…”
Section: Resultssupporting
confidence: 74%
“…9A). Previous work suggested that Met-mediated prevention of apoptosis could be independent from its catalytic activity (15). Our data clearly indicate that the mechanisms by which Met triggers the antiapoptotic response are also strictly reliant on its kinase activity.…”
Section: Resultssupporting
confidence: 74%
“…To test vulnerability to injury, we first evaluated the response of MetLivKO mice to apoptotic stimuli induced by Fas antibody. This was of considerable interest because not only does pretreatment with rhHGF before anti-Fas antibody injection demonstrate a potent dose-dependent inhibition of liver apoptosis and lethal hepatic failure (19), but it was recently shown that direct binding between c-Met and Fas receptor inhibited Fas activation and thus prevented apoptosis (28). Massive hepatocyte death and hemorrhagic liver destruction in MetLivKO mice began within the first 2-4 h after injection of the Jo-2 antibody; and by 8 h, 80% of the animals died of acute liver failure.…”
Section: Resultsmentioning
confidence: 99%
“…2 D-F ), implying that Fas expression is not affected by the lack of c-Met under physiological conditions. However, the observed sensitivity of the MetLivKO mice to Fas-mediated apoptosis may be due to the reduced amount of c-Met protein and thus attenuated Met-Fas sequestration (28). Alternatively, the loss of antiapoptotic signaling by HGF͞c-met in MetLivKO mice may potentiate the death-inducing function of the Fas ligand (29).…”
Section: Resultsmentioning
confidence: 99%
“…Two decades ago, profound studies were published about the physiological aspects of HGF in health and development [29,30]. In recent years, however, several groups have focused on assessing HGF during inflammation and cancer [10].…”
Section: Discussionmentioning
confidence: 99%